Urgensi Sarana dan Prasarana Bimbingan dan Konseling di Yayasan Islamiyah Medan - Nurussakinah Daulay; Aika Azzura; Fadira Al Mefa[; Latifa Rotonga[; Miftahul Hasana Putri; Rafiqah Umry Siregar (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study has a goal, namely to find out the feasibility and completeness leadership and advice facilities and infrastructure at the Madrasah Islamiyah Foundation school in Medan. This approach uses a qualitative type of phenomenological research. The research was conducted using observation and interview methods. This study uses data analysis techniques taken from Miles and Huberman's analytical model: data reduction, data presentation, and inference. Results of this study explain that the Medan Islamic Madrasah Foundation does not meet the standards of orientation and counseling facilities and infrastructure due to costs and limited land that are also affected by COVID-19, resulting in the implementation of services not being carried out effectively and efficiently. Keywords: Guidance counseling, infrastructure, facilities